Examining determinants of career progression and competency enhancement among nurses - Pitriyanti Pitriyanti; Irna Nursanti; Febrian Rahmat Suwandi (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Career progression in nursing is achieved through enhanced competencies gained from formal, structured education, relevant informal learning, and clinical experience. However, the implementation of career pathways in several hospitals remains suboptimal. Purpose: To examine the key factors influencing the development of nurses' career levels and competencies at Haji Abdoel Majid Batoe Hospital, Batang Hari Jambi. Method: A quantitative correlational study with an ex post facto design was conducted at Haji Abdoel Majid Batoe Hospital between October and November 2024. Data were collected using a questionnaire from a proportionally randomized sample of 141 nurses. Data analysis was carried out using multiple linear regression. Results: Supervisor support was the most influential factor affecting nurses' career level and competency development (p = 0.000). Overall, 38.5% of the variance in career level and competency development could be explained by job satisfaction, supervisor support, and management support, while the remaining 61.5% was attributed to other variables outside the model. Conclusion: Job satisfaction, supervisor support, and management support significantly contribute to the development of nurses' career levels and competencies. It is recommended that hospital management, particularly the nursing committee, implement a policy of monthly mentoring sessions for nurses undergoing competency assessments for career advancement.